The impact of invented spelling on phonemic awareness - Martins, Margarida Alves (2015)
The objective of this study was to assess the impact of a training programme, designed to make preschool-age children’s invented spelling evolve, on their phonemic awareness. The participants were 90 children who were divided into 3 experimental and 3 control groups based on the nature of their invented spelling. Children’s phonemic skills were evaluated in a pre-test and a post-test. In between the experimental groups underwent the training program. The experimental groups achieved greater progress in the phonemic tests than the control groups. The training’s impact on those tests differed depending on the level of the children’s invented spelling.